DOSE AND DURATION OF CALCIUM SUPPLEMENTATION ON PRE-ECLAMPSIA: A CASE CONTROL STUDY: Dosis dan Lama Suplementasi Kalsium Pada Pre-Eclampsia: Studi Kasus Kontrol - Eny Qurniyawati; Retno Adriyani; Sigit Ari Saputro; Nayla Mohamed Gomaa Nasr (Universitas Airlangga, 2023)
Background: Pre-eclampsia is one of the causes of high maternal morbidity and mortality. The WHO has recommended calcium supplementation based on dose and duration in pregnant women to reduce the risk of pre-eclampsia. However, the calcium supplementation program in Indonesia is not following the WHO recommendations. Objective: This study aimed to analyze the dose and duration of calcium supplementation on the occurrence of pre-eclampsia. Methods: This research is an observational study with a case-control design. The study was conducted from June to August 2021. The study participants are pregnant women in the third trimester in Madiun District, consisting of 42 case groups and 98 control groups with random cluster sampling. Simple logistic regression was used to analyze the relationship between dose and duration of calcium supplementation variables on the variable of pre-eclampsia. Results: Calcium dose showed calcium consumption < 3 doses/day had odds of 2.54 times compared to calcium intake 3 doses/day [95%CI = 1.02-6.35]. The duration of calcium supplementation showed that calcium administration after 20 weeks had odds of 0.45 times [95%CI = 0.21-0.98] compared to calcium administration before 20 weeks of gestation on the occurrence of pre-eclampsia. Conclusion: Calcium supplementation based on dose and duration was associated with the occurrence of pre-eclampsia. It was recommended for pregnant women to consume calcium supplements with the right dose and duration to reduce the risk of pre-eclampsia.